Search Engines and Beyond: A Toolkit for Finding Free Online Resources for Science, Technology and Engineering. - Nedelina Tchangalova; Francy Stilwell (Issues in Science and Technology Librarianship, 2012)
The article reviews several websites related to science and technology, including the Bielefeld Academic Search Engine (BASE) at www.base-search.net, E-Print Network at www.osti.gov/eprints/ and ScienceCinema at www.osti.gov/sciencecinema/.